The effects of upper limb posture and a sub-maximal gripping task on corticospinal excitability to muscles of the forearm. (April 2016) - Forman, Davis A.; Baarbé, Julianne; Daligadu, Julian; Murphy, Bernadette; Holmes, Michael W.R.
Abstract: Variations in handgrip force influences shoulder muscle activity, and this effect is dependent upon upper limb position. Previous work suggests that neural coupling between proximal and distal muscles with changes in joint position is a possible mechanism but these studies tend to use artificially constrained postures that do not reflect activities of daily living. The purpose of this study was to examine the effects of upper limb posture on corticospinal excitability to the forearm muscles during workplace relevant arm positions. Motor evoked potentials (MEPs) were elicited in four forearm muscles via transcranial magnetic stimulation at six arm positions (45°, 90° and 120° of humeral elevation in both the flexion and abduction planes). MEPs were delivered as stimulus–response curves (SRCs) at rest and at constant intensity during two gripping tasks. Boltzmann plateau levels were smaller for the flexor carpi radialis in flexion at 45° versus 90° ( p = 0.0008). Extensor carpi radialis had a greater plateau during flexion than abduction ( p = 0.0042). Corticospinal excitability to the forearm muscles were influenced by upper limb posture during both the resting and gripping conditions. This provides further evidence that upper limb movements are controlled as a whole rather than segmentally and is relevant for workplace design considerations.